2022
DOI: 10.1016/j.meegid.2022.105208
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic change of SARS-CoV-2 variants in Sierra Leone

Abstract: Since the beginning of the SARS-CoV-2 pandemic, the emergence of multiple new variants posed an increased risk to global public health. The aim of this study is to investigate SARS-CoV-2 variants and possible transmission of variants of concern (VOCs) in Sierra Leone. A total of 65 nasal swab samples were collected from COVID-19 cases in Sierra Leone, among which 24 samples were collected during the second wave and 41 samples were collected during the third wave. Nanopore sequencing generated 54 SARS-CoV-2 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The use of next-generation sequencing technology can be beneficial in several steps of an epidemic response [13], among them, pathogen identification [14], tracing the origins of the agent [15][16][17], and monitoring its spread [18][19][20][21][22][23] and evolution [17,24,25], as well as supporting development of diagnostic solutions and new therapeutic target discovery [26]. Even though there are different approaches to full-genome sequencing, the multiplex PCR amplicon method is currently one of the cheapest, while also proving to be superior to capture-based sequencing in the analysis of challenging samples [4].…”
Section: Discussionmentioning
confidence: 99%
“…The use of next-generation sequencing technology can be beneficial in several steps of an epidemic response [13], among them, pathogen identification [14], tracing the origins of the agent [15][16][17], and monitoring its spread [18][19][20][21][22][23] and evolution [17,24,25], as well as supporting development of diagnostic solutions and new therapeutic target discovery [26]. Even though there are different approaches to full-genome sequencing, the multiplex PCR amplicon method is currently one of the cheapest, while also proving to be superior to capture-based sequencing in the analysis of challenging samples [4].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries setting, conventional next‐generation sequences are commonly challenging and requires extensive bioinformatics expertise. Moreover, the Oxford MinION, a third‐generation nanopore‐based platform has been used in several LMICs including India, Bangladesh, Indonesia, and others for SARS‐CoV‐2 nationwide surveillance studies 31–38 . This study represents a pioneering genomic surveillance effort, involving systematic sampling in Mongolia for respiratory viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that SARS-CoV-2's introduction led to local transmission events. A previous study showed that, in Sierra Leone, the second COVID-19 wave was mainly caused by the R1 lineage, while the third COVID-19 wave was dominated by the spread of the B.1.617.2 lineage (Delta variant), and further phylogenetic analysis revealed that multiple introductions of SARS-CoV-2 into Sierra Leone subsequently led to clusters and community transmission in the country ( 29 ). Similarly, most of Africa's COVID-19 cases that were considered to constitute the third wave of the pandemic were either imported cases or were triggered by imported COVID-19 cases ( 28 ).…”
Section: Discussionmentioning
confidence: 99%